Isolation and Identification of Thermophilic Bacteria from Lahendong Hot Spring, North Sulawesi - Christiana Abrita Nathania Corneles; Feky Mantiri; Marina Singkoh (JURNAL BIOS LOGOS, 2023)
Thermophilic bacteria are a group of procaryotic organisms that can grow in high temperature around 450C until 900C. Thermophilic bacteria are able to produce lipase thermostable enzyme. Lipase thermostable enzymes produced from thermophilic bacteria are able to catalyze the hydrolysis of triglycerides into glycerol and free fatty acids and the synthesis of esters in organic solvents. Lipase thermostable enzymes are potential to be used in industrial production. Lipase enzymes have been used for the production of laundry detergents as additives or to replace chemical detergents because of their environmental friendliness. This research was aimed to isolates and identified themophilic bacteria from Lahendong hot springs, North Sulawesi and to conduct the morphological characterization, biochemical test, and molecular identification with 16S rRNA. Results showed that isolates obtained from the- Lahendong hot spring have high similarities with Geobacillus kaustophilus, Bacillus cereus, and Geobacillus lituanicus. The three isolates are able to produce lipase thermostbale enzyme.